Evaluation of endometrial abnormalities in breast cancer patients on tamoxifen therapy - Hossain, Silvia; Anwar, Begum Rokeya; Sharmin, Foujia; Siddiqua, Ayesha; Hossain, M. Saklayen (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Background: Breast cancer is the most common malignancy in women. Tamoxifen, widely used as adjuvant therapy, has anti-estrogenic effects on breast tissue but may induce endometrial changes due to estrogenic stimulation. To evaluate endometrial abnormalities in postmenopausal breast cancer patients receiving tamoxifen therapy. Methods: This cross-sectional study was conducted at the Department of Gynaecological Oncology, NICRH, Dhaka, over one year. Seventy-five postmenopausal breast cancer patients who had received tamoxifen for more than six months were enrolled. All underwent transvaginal ultrasound (TVS) and 32 patients subsequently had histopathological evaluation. Data were analyzed using SPSS v23. Results: The mean age was 58.03±7.96 years. TVS revealed endometrial thickness of 4–7.9 mm in 58.6%, 8–11.9 mm in 8%, 12–15.9 mm in 12%, 16–19.9 mm in 6.7% and ≥20 mm in 14.6% of patients, with a mean thickness of 11.22±6.68 mm. Thickness ≥8 mm was significantly associated with longer tamoxifen use (p<0.05). Histopathology (n=32) showed 25% normal endometrium, while 75% had abnormalities: polyps (28.1%), hyperplasia without atypia (25%), hyperplasia with atypia (9.4%), atrophy (9.4%) and carcinoma (3.1%). A significant correlation was found between TVS findings and histopathology (p=0.044). Conclusions: Nearly two-fifths of patients developed endometrial thickening >8 mm and three-quarters of those biopsied had abnormal histopathology, including hyperplasia with atypia and carcinoma. Long-term tamoxifen therapy in postmenopausal women may predispose to endometrial pathology, warranting regular surveillance with TVS and prompt biopsy for suspicious cases.